Integrating Analgesic Doses and Pain Trend Analysis: A Novel Clinical Support System - Shih-Chieh Yang; Chih-Cheng Wu (International Journal of Pain Management, 2025)
Background Prescribing appropriate analgesics with optimal dosages based on patients' pain severity is challenging, especially when multiple painkillers are involved. Tracking and analyzing the effectiveness of analgesics and their dosages over time is crucial for pain management. Existing systems lack the ability to integrate analgesic equivalent doses with temporal trends in pain scores, hindering effective decision-making. Methods We developed a Clinical Support System that calculates the daily oral morphine equivalent dose and analyzes trends in consumed equivalent doses of analgesics. The system provides a graphical user interface that displays medication prescriptions, actual medication usage, and pain scores. It offers features such as correlating analgesic drug usage with pain intensity, trend analysis of analgesic drug usage and pain intensity, and identification of effective oral morphine equivalent doses. Results The system overcomes previous barriers in drug analysis by providing real-time calculation of oral morphine equivalents and trend analysis of pain duration. It assists physicians in prescribing appropriate and safe medication dosages, enhancing medication safety for patients. Conclusions Our clinical support system offers a comprehensive solution for analyzing trends in consumed equivalent doses of analgesics. It integrates medication prescriptions, actual usage, and pain scores, providing decision-making support for pain management.
Keywords: Pain Management